2010
DOI: 10.1007/s11910-010-0093-7
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Strategies for Diabetic Neuropathy

Abstract: Diabetes is the leading cause of peripheral neuropathy globally. Duration of diabetes, glycemic control, and preexisting cardiovascular risk factors independently correlate with the development and progression of diabetic peripheral neuropathy as well as cardiovascular autonomic neuropathy. The pathogenesis of diabetic neuropathy remains unclear, although insulin resistance, oxidative stress, mitochondrial dysfunction, abnormal glucose metabolism, advanced glycation end products, neurotrophic factors, and prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 54 publications
(51 reference statements)
0
23
0
Order By: Relevance
“…The observed increase in small myelinated fibre profiles in sciatic nerve trunk may represent large fibre neuropathy, with demyelination of larger fibres [25], and hence smaller apparent cross sectional area both in the nerve fibre and somata. Myelin damage could affect sensory fibres or motor axons, although hyperglycaemia has been shown to affect sensory fibres to a greater extent than motor axons [35]. Activated caspase-3 coexpression with NF200 in DRG neurons is also consistent with this interpretation.…”
Section: Discussionmentioning
confidence: 59%
“…The observed increase in small myelinated fibre profiles in sciatic nerve trunk may represent large fibre neuropathy, with demyelination of larger fibres [25], and hence smaller apparent cross sectional area both in the nerve fibre and somata. Myelin damage could affect sensory fibres or motor axons, although hyperglycaemia has been shown to affect sensory fibres to a greater extent than motor axons [35]. Activated caspase-3 coexpression with NF200 in DRG neurons is also consistent with this interpretation.…”
Section: Discussionmentioning
confidence: 59%
“…He goes on to describe that the Kumomoto study (Shichiri 2000) revealed a similar effect in people with type 2 diabetes, which was later supported by the UKPDSStudy Group 1998. In 2010, Habib 2010 and Stolar 2010 both emphasized the DCCT findings. Stolar 2010 go on to describe the UKPDS Study Group 1998 as well.…”
Section: Discussionmentioning
confidence: 99%
“…Intensive metabolic control of blood glucose reduces the incidence of new clinically detected neuropathy, but diabetes patients can still develop DPN (78). Intensified glucose-lowering therapy increases the risk of hypoglycemic episodes and can even be dangerous (79,80).…”
Section: Activation Of Plcβ3 Causes An Increase In Intracellular Camentioning
confidence: 99%